Games In Islamic Religious Education: A Quantitative Study Of Student Participation At Mts Nahdatul Islam School - Nur, Mudia Hawa; Tanjung, Alfian (The Islamic Education and Multiculturalism Foundation, 2026)
AbstrakPenelitian ini membahas penerapan gamifikasi dalam pembelajaran Pendidikan Agama Islam serta pengaruhnya terhadap keterlibatan siswa di Madrasah Tsanawiyah Nahdatul Islam. Permasalahan penelitian berangkat dari rendahnya partisipasi aktif siswa dalam proses pembelajaran yang cenderung monoton dan kurang interaktif. Tujuan penelitian ini adalah untuk menganalisis sejauh mana penggunaan gamifikasi berkontribusi dalam meningkatkan keterlibatan siswa baik secara kognitif, emosional, maupun perilaku dalam pembelajaran Pendidikan Agama Islam. Penelitian ini menggunakan pendekatan kuantitatif dengan metode survei. Sampel penelitian terdiri dari siswa Madrasah Tsanawiyah Nahdatul Islam yang dipilih melalui teknik pengambilan sampel secara proporsional. Instrumen penelitian berupa angket tertutup menggunakan skala pengukuran yang telah diuji validitas dan reliabilitasnya. Data dianalisis menggunakan statistik deskriptif dan inferensial melalui uji regresi untuk mengetahui hubungan dan pengaruh antarvariabel. Hasil penelitian menunjukkan bahwa gamifikasi berpengaruh positif dan signifikan terhadap keterlibatan siswa dalam pembelajaran Pendidikan Agama Islam. Penerapan elemen permainan seperti poin, tantangan, dan penghargaan terbukti mampu meningkatkan motivasi belajar serta partisipasi siswa dalam kegiatan kelas. Dengan demikian, gamifikasi dapat menjadi strategi pembelajaran inovatif untuk meningkatkan kualitas pembelajaran Pendidikan Agama Islam di tingkat madrasah. Kata Kunci: Gamifikasi, Pendidikan Agama Islam, Keterlibatan Siswa, Motivasi Belajar, Madrasah Tsanawiyah AbstractThis study examines the use of gamification in Islamic Religious Education learning and its influence on student engagement at Madrasah Tsanawiyah Nahdatul Islam. The research problem is based on the low level of student participation in learning activities that are often considered monotonous and less interactive. This study aims to analyze the extent to which gamification contributes to improving students’ engagement in Islamic Religious Education, including cognitive, emotional, and behavioral aspects. The research employed a quantitative approach using a survey method. The sample consisted of students at Madrasah Tsanawiyah Nahdatul Islam selected through proportional sampling. Data were collected through a structured questionnaire using a measurement scale that had been tested for validity and reliability. The data were analyzed using descriptive statistics and inferential analysis, particularly regression testing, to determine the relationship and effect between variables. The findings show that gamification has a positive and significant effect on student engagement in Islamic Religious Education learning. The application of game elements such as points, challenges, and rewards was proven to increase students’ learning motivation and active participation during classroom activities. Therefore, gamification can be considered an innovative instructional strategy to enhance the effectiveness and quality of Islamic Religious Education learning at the madrasah level.Keywords: Gamification, Islamic Religious Education, Student Engagement, Learning Motivation, Madrasah Tsanawiyah